Scaling of metal forming processes. (2017) - Al-Tamimi, A.; Darvizeh, R.; Davey, K.
Abstract: A new approach to scaled experimentation has appeared in the recent literature, which is founded on the idea that scaling can be achieved by scaling space itself. The idea that space expands and distorts is not new to physics (cosmology and general relativity in particular) but the idea that scaling space can provide insight into scaled metal forming experimentation is considered novel. The concept involves a portion of space identified by a control volume (free to move and distort) coupled to a version residing in a scaled space. The processes under investigation are contained within the control volumes and may include die sets and any aspects deemed important to the success of the scaled experiment. The physics in the two spaces are described using transport equations and are deemed to possess finite similitude if found to be proportional in some sense. Finite similitude always exists in continuum mechanics for isotropic scaling and it is shown in this paper how the concept can be used to design experiments. Numerical and experimental trials are performed to reveal the benefits and validity of the new scaling approach.